Unconventional Transformations of Morita–Baylis–Hillman Adducts - Calcatelli, Alessio; Cherubini-Celli, Alessio; Carletti, Edoardo; Companyó, Xavier (Synthesis, 2020)
Morita–Baylis–Hillman (MBH) adducts are versatile starting materials widely employed in Lewis base catalysis. A myriad of different transformations have been reported based on either allylic alkylations with stabilised nucleophiles or annulations with diverse dipolarophiles. Apart from these two conventional types of reactivity, MBH adducts have recently been implemented in alternative and complementary catalytic strategies, including: (i) one-pot and cascade transformations, where additional chemical bonds are formed following the asymmetric allylic alkylation event in a single synthetic operation; (ii) regioselective α-allylations for the synthesis of trisubstituted alkenes; and (iii) dual activation strategies, involving Lewis base catalysis together with transition metal complexes or light, enabling allylic alkylations with nonstabilised nucleophiles and cascade processes. The present Short Review summarises the most significant unconventional catalytic transformations of racemic MBH adducts reported within the last decade.1 Introduction2 Multi-Step Single-Vessel Transformations (path iii)2.1 One-Pot Transformations2.2 Cascade Transformations3 α-Allylations (path iv)3.1 SN2′ Mechanism3.2 SN2′–SN2 Mechanism3.3 Miscellaneous Mechanisms4 Dual Activation (path v)4.1 MBH Adduct as Electrophile4.2 MBH Adduct as Nucleophile5 Summary and Outlook
Keywords: Morita–Baylis–Hillman adducts; allylic alkylation; dipolar annulations; one-pot transformations; cascade transformations; α-allylations; Lewis base catalysis; dual activation